Fan Loyalty Toward International Football Team: The Role of Brand Image - Dwi Irianto; Dwi Kartikasari (Politeknik Negeri Bandung, 2020)
The study of fan loyalty in sports marketing mostly is focused on spectator attachment and brand athlete. However, lack of studies examines the fan loyalty formulation toward the international team using brand image. This study aims to examine the influence of two brand image dimensions (attributes and benefits) in creating fan loyalty toward the international team. This study applies the covariance-based structural equation model for analyzing the data. The sample consists of 335 international team football fans in Indonesia. These results reveal that both attributes and benefits are pivotal factors in influencing attitudinal loyalty as well as behavioral loyalty. Further, the result shows that the effect of attributes on attitudinal loyalty is higher compared to behavioural loyalty. These findings extend the existing knowledge on the relationship between brand image and customer loyalty in a sports context and provide useful implications for practitioners to retain their fan loyalty.